Pengaruh Kompetensi Profesional Guru,Motivasi Kerja Dan Semangatkerja Terhadap Kinerja Guru Di SMP Kadijah Padang - Sudirman, Sudirman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
This study aims to determine the effect of teacher professional competence, work motivation and work enthusiasm both individually and collectively on teacher performance at SMP Kadijah Padang. The subjects of this study were all 32 teachers at SMP Kadijah Padang. This research is an ex-post facto research. The data collection method uses a Likert scale model questionnaire for the variables of Teacher Professional Competence, Work Motivation and Work Spirit, while the Teacher Performance variable uses the questionnaire method, and documentation from the Principal. The data analysis technique used to test the hypothesis is the regression analysis technique. The results of the study show that (1) there is a significant effect of teacher professional competence on teacher performance in SMP Kadijah Padang as evidenced by Fcount < Ftable (2.026 < 4.22), (2) there is a significant effect of work motivation on teacher performance - teachers at SMP Kadijah Padang as evidenced by: Fcount < Ftable (2.451 < 4.22), (3) there is a significant effect of morale on the performance of teachers at SMP Kadijah Padang as evidenced by: Fcount > Ftable (17.141 > 4, 22); the contribution of work enthusiasm to teacher performance is 39.73%; (4) there is a significant influence of the teacher's professional competence, work motivation and work enthusiasm together on the performance of teachers at SMP Kadijah Padang as evidenced by: Fcount > Ftable (5.832 > 3.01); the contribution of teacher professional competence, work motivation and work enthusiasm together to teacher performance is 42.16%.